User Manual. Training Manual Terra-i. - Reymondin, Louis; Paz-García, Paula; Tello Dagua, Jhon Jairo; Coca-Castro, Alejandro; Bautista, Oscar; Menzinger, Bernadette (International Center for Tropical Agriculture, 2019)
The user manual describes the installation process of the Terra-i system as well as the necessary tools for its functioning. Input data acquisition procedures used by Terra-i are also described. Finally, it shows the insights, methods and formats involved in each step of the pre-processing stage.